2016
DOI: 10.1126/science.aaf6284
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic glycolysis promotes T helper 1 cell differentiation through an epigenetic mechanism

Abstract: Aerobic glycolysis (the Warburg effect) is a metabolic hallmark of activated T cells, and has been implicated in augmenting effector T cell responses including expression of the pro-inflammatory cytokine interferon (IFN)-γ via 3′ untranslated region (3′UTR)-mediated mechanisms. Here we show that lactate dehydrogenase A (LDHA) is induced in activated T cells to support aerobic glycolysis, but promotes IFN-γ expression independently of its 3′UTR. Instead, LDHA maintains high levels of acetyl-CoA to enhance histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
621
4
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 635 publications
(648 citation statements)
references
References 38 publications
19
621
4
4
Order By: Relevance
“…Moreover LDH activity was increased in RA synovial tissues compared to healthy controls thus suggesting an increased glycolytic metabolism in the RA synovial joints [46]. The key role of LDH in promoting inflammation was also recently highlighted in the recent paper by Peng et al [47] where they identified that LDH-A is important to promote T-cell effector functions by increasing acetylation and IFN-γ transcription.Lactate transporters are becoming increasingly relevant in the pathogenesis of RA. Indeed, it has been recently found that monocarboxylate lactate transporter 4 (MCT4) is upregulated by RA synovial fibroblasts (RASF) compared to osteoarthritis SF.…”
mentioning
confidence: 84%
“…Moreover LDH activity was increased in RA synovial tissues compared to healthy controls thus suggesting an increased glycolytic metabolism in the RA synovial joints [46]. The key role of LDH in promoting inflammation was also recently highlighted in the recent paper by Peng et al [47] where they identified that LDH-A is important to promote T-cell effector functions by increasing acetylation and IFN-γ transcription.Lactate transporters are becoming increasingly relevant in the pathogenesis of RA. Indeed, it has been recently found that monocarboxylate lactate transporter 4 (MCT4) is upregulated by RA synovial fibroblasts (RASF) compared to osteoarthritis SF.…”
mentioning
confidence: 84%
“…In recent years, it has been shown a strong link between irreversible metabolic reactions, epigenetic patterns and gene expression patterns [13][14][15]34] as an evidence of a new and unified scenario. In this context, the phenomenological and thermodynamic approach could provide a solid basis for a new systemic conception.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the phenomenological and thermodynamic approach could provide a solid basis for a new systemic conception. In fact, it is plausible that living systems originate from a high value of the rate of entropy dissipation to reach a stationary minimum dissipation phase [14,15,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial acetyl-CoA cannot directly cross the mitochondrial membrane but, instead, is transferred to the cytosol via citrate export and conversion to acetyl-CoA by ATP citrate-lyase (ACLY) (6). ACLY has been shown to regulate histone acetylation levels and influence gene regulation in diverse mammalian cell types (19,21,(27)(28)(29), and histone acetylation is responsive to glucose availability in an ACLY-dependent manner (19,21,30). We have shown previously that Acly silencing impairs histone acetylation and expression of select genes such as Glut4 during 3T3-L1 adipocyte differentiation (18).…”
mentioning
confidence: 99%